Gamma irradiation mediated production improvement of some myco-fabricated nanoparticles and exploring their wound healing, anti-inflammatory and acetylcholinesterase inhibitory potentials - El-Sayed R. El-Sayed; Doaa S. Mansour; Reham M. Morsi; Hanan A. Abd Elmonem (Scientific Reports, 2023)
Abstract In the current scenario, scaling up the microbial production of nanoparticles with diverse biological applications is an emerging prospect for NPs’ sustainable industry. Thus, this paper was conducted to develop a suitable applicative process for the myco-fabrication of cobalt-ferrite (CoFeNPs), selenium (SeNPs), and zinc oxide (ZnONPs) nanoparticles. A strain improvement program using gamma irradiation mutagenesis was applied to improve the NPs-producing ability of the fungal strains. The achieved yields of CoFeNPs, SeNPs, and ZnONPs were intensified by a 14.47, 7.85, and 22.25-fold increase from the initial yield following gamma irradiation and isolation of stable mutant strains. The myco-fabricated CoFeNPs, SeNPs, and ZnONPs were then exploited to study their wound healing, and anti-inflammatory. In addition, the acetylcholinesterase inhibition activities of the myco-fabricated NPs were evaluated and analyzed by molecular docking. The obtained results confirmed the promising wound healing, anti-inflammatory, and acetylcholinesterase inhibition potentials of the three types of NPs. Additionally, data from analyzing the interaction of NPs with acetylcholinesterase enzyme by molecular docking were in conformation with the experimental data.